EFFECTIVENESS OF USING RIVER INSECT LARVAE AS AN INDEX OF CU, ZN AND AS CONTAMINATIONS IN RIVERS, JAPAN (GEOMATE Journal, 2017)
Analysis of Dobsonfly (a kind of Megaloptera, Protohermes grandis) larvae forconcentrations of Cu and Zn was found to be an effective method of determining levels of Cu and Zncontamination of rivers in metal mine areas and non-metal mine catchments. Metal concentration inDobsonfly larvae was used as an index of metal contamination because the amount of metal concentration inDobsonfly larvae decreased with the dry weight of the larvae and also on the degree of metal present in theriver water. Dobsonfly makes an excellent tool for contamination evaluation because of their easyclassification, wide distribution and commonness. Furthermore, due to their relatively lengthy 2-3 yearlifespan, river contamination assessment over a long term could be performed. In this study, Cu, Zn and Asconcentrations in river insect larvae in metal mine areas were found to be higher than those in non-minecatchments.